THE CHALLENGES THAT THE INTERNATIONAL COURT OF JUSTICE HAS TO FACE - Peruana de Derecho Internacional, Sociedad (2021)
In the article, we will identify some of the challenges that the ICJ has to face during the 75thanniversary of its inaugural session. Throughout the year, the Court has consolidated herself asan effective mechanism to resolve international disputed, however after three quarters of acentury, the time has come to identify which are the aspects that should be updated so that itcontinues to maintain its utility throughout the 21st century. International society has evolved alot since the Court began to function, so I consider that the time has come to study the strengthsand weaknesses that it has, in order to further the strengthening the former and correcting thelatter with the sole objective of adapting this dispute resolution mechanism challenges to beaddressed in the near future.